D-Lactic Acidosis: An Underrecognized Complication of Short Bowel Syndrome - N. Gurukripa Kowlgi; Lovely Chhabra (Gastroenterology Research and Practice)
D-lactic acidosis or D-lactate encephalopathy is a rare condition that occurs primarily in individuals who have a history of short bowel syndrome. The unabsorbed carbohydrates act as a substrate for colonic bacteria to form D-lactic acid among other organic acids. The acidic pH generated as a result of D-lactate production further propagates production of D-lactic acid, hence giving rise to a vicious cycle. D-lactic acid accumulation in the blood can cause neurologic symptoms such as delirium, ataxia, and slurred speech. Diagnosis is made by a combination of clinical and laboratory data including special assays for D-lactate. Treatment includes correcting the acidosis and decreasing substrate for D-lactate such as carbohydrates in meals. In addition, antibiotics can be used to clear colonic flora. Although newer techniques for diagnosis and treatment are being developed, clinical diagnosis still holds paramount importance, as there can be many confounders in the diagnosis as will be discussed subsequently.